Generation and transport of atomic lithium during the exposure of liquid metals to hot plasmas in TJ-II. (December 2018) - Tabarés, F.L; Oyarzábal, E.; Tafalla, D.; Martín-Rojo, A.B.; Ochando, M.A; Medina, F.; McCarthy, K.J.; Zurro, B.; López-Miranda, B.; Pastor, I.
Highlights: The ejection velocities for Li from both liquid metals are basically the same. There is no significant evolution with temperature of the kinetic energy of the ejected atom over the temperature range recorded by the pyrometer (T > 150 ºC). Hints of higher energies at T < 150 ºC were found, with values up to 0.5 eV. The kinetic energy at high temperatures is a factor of 3 to 4 larger that the corresponding thermal energies, but also several times smaller than the expected sputtering energies. There is no difference in the toroidal dispersal of Li and He ions around their sources, which can be ascribed to classical thermalization with the plasma ions. Abstract: A full campaign of comparative Li/LiSn/Sn testing has been initiated in TJ-II stellarator plasmas. Solid and liquid samples of the three candidates, in a Capillary Porous System (CPS) arrangement, have been exposed to the edge plasma and the associated perturbation on the plasma has been recorded. In this work, only studies on Li and LiSn alloys are reported. The surface temperature of the liquid metal/CPS samples (a tungsten mesh impregnated with SnLi or Li) has been measured during plasma pulses with milliseconds resolution by pyrometry and radial profiles of Li, Li +, and Balmer Hα were recorded together with the electron edge parameters. A simple 1D model, based on the density decay, was applied to the data, allowing for the evaluation of the kinetic energy (Ek ) of ejected atomic species while their residence time at the edge was determined by monitoring the ratio of first ion/neutral emission light intensities. Some evolution of Ek with sample temperature was seen for Li atoms, this being likely associated to the different relative contributions of sputtered/evaporated atoms, although values below 0.25 eV were found for sample temperatures above 500 K. The recorded Li + /Li ratios were analyzed through a simple model accounting for several mechanisms for the dispersal of the injected impurity away from the injection location. The same model was applied to injected He atoms (high recycling impurity) in order to check for prompt redeposition of Li. A transition from sputtering driven to evaporation of Li is observed with increasing temperature. Furthermore, no evidence of prompt redeposition is observed in our conditions.